(untitled) (Journal of economic and management development research, 2025)
This paper systematically sorts out the development course of economics as a discipline in China, covering the introduction of Western economics in the early stage, the establishment of Marxist political economics, and the construction of the theoretical system of economics with Chinese characteristics after the reform and opening-up. Combining the characteristics of vocational education, it explores how to balance the relationship between ideological education and market demand orientation in the professional teaching of economic management. The research shows that economics education must adhere to the guiding position of Marxism, while closely integrating with the practice of China’s economic development, to cultivate applied talents who are proficient in both theory and practice. This paper proposes an innovative model of vocational education featuring "ideological and political guidance, market orientation, and competence-based", which realizes the organic unity of ideological education and vocational skills training through the reconstruction of curriculum system, the innovation of teaching methods, and the deepening of industry-education integration. It provides theoretical support and practical paths for the reform of economics education in vocational colleges.